WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Le contrôle social réservé aux femmes: entre prison, justice et travail social - Cardi, Coline (Déviance et Société, 2007)
Très peu d’études sociologiques françaises ont tenté une approche de la déviance en termes de genres: la sous-représentation statistique des femmes dans la sphère pénale suffit souvent à les écarter des analyses. Pourtant, prendre pour objet la déviance des femmes permet d’éclairer le fonctionnement du processus pénal, notamment dans son rapport avec des dispositifs parapénaux qui contribuent à distribuer de façon différentielle la déviance des hommes et celle des femmes. Ainsi, partir de la marge, que représentent les femmes incarcérées, est un moyen d’interroger le centre et de saisir en quoi, s’il faut penser la prison en lien avec l’ordre social, il faut également et conjointement la penser en lien avec l’ordre sexué et les normes qui lui sont liées.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; justice sociale; premier cycle; prison; périodes historiques; régions géographiques; sciences humaines; thématiques; travail social; trs1205; violences

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

‘Psy’, ‘coach’ et travail dans ‘l'entreprise du couple’: les femmes en première ligne dans Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle - Jonas, Irène (Actes du 4e Congrès international des recherches féministes dans la francophonie plurielle, 2007)
Avec les revendications féministes, la famille a connu de nombreuses et profondes transformations au cours de ces dernières années. Elles ont pourtant été inégalement réalisées et, lorsqu’elles le furent, elles n’ont pas pour autant aplani toutes les difficultés. Ces textes traitent de l’accouchement, de l’avortement, de la contraception, du divorce, du mariage et de la recomposition familiale, des relations de couple, aux quatre coins de la francophonie: le Brésil, la France, la Grèce, le Sénégal, la Suisse et le Québec. Situations forcément différentes et pourtant questions communes susceptibles d’élargir la réflexion transfrontalière face à une institution, la famille, partout remise en cause, avec les premiers balbutiements de l’égalité des sexes. Textes de Fatou Binetou Dial, Nikoletta Chardalia, Irène Jonas, Françoise Le Borgne-Uguen, Ana Liesi Thurler, Sylvie Perrier, Éliane Perrin et son équipe, Isabelle Puech, Catherine Pugeault-Cicchelli, Lucia Scavone, Carmen Susana Tornquist, Hélène Trellu et une introduction de Marie-Blanche Tahon.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; brésil; care; corps; cours; discipline; france; francophonie; grèce; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; suisse; sénégal; thématiques; travail; travail social; trs1205